Sausage Preservation Using Films Composed of Chitosan and a Pickering Emulsion of Essential Oils Stabilized with Waste-Jujube-Kernel-Derived Cellulose Nanocrystals - Haoyu Chen; Keqi Xin; Qunli Yu (Foods)
The purpose of this study was to prepare Pickering emulsions stabilized by waste jujube kernel cellulose nanocrystals (CNC) using composite essential oils (EOs) (i.e., cinnamon essential oil [CIN] combined with clove essential oil [CL]). The Pickering emulsions were blended with chitosan (CS) to generate a composite film (CS/CNC/EOs Pickering emulsions). We evaluated the mechanical properties, barrier properties, and microstructures of CS/CNC/EOs bio-based packaging films containing different concentrations of EOs. In addition, the fresh-keeping effects of the composite membranes on beef sausages were evaluated over a 12-day storage period. Notably, the EOs exhibited good compatibility with CS. With the increase in the EOs concentration, the droplet size increased, the composite films became thicker, the elongation at break decreased, the tensile strength increased, and the water vapor permeability decreased. When the composite films were used for preserving beef sausages, the antioxidant and antibacterial activity of the membranes improved as the concentration of EOs increased, effectively prolonging the shelf life of the sausages. Composite membranes with an EOs concentration of 2% exerted the best fresh-keeping effects. Overall, owing to their antioxidant and antimicrobial properties, the bio-based composite films prepared using CS/CNC/EOs Pickering emulsions demonstrated immense potential for application in the packaging of meat products.